Resort development and touristic capital of place - Stock, Mathis (My University, 2014)
Resort development raises not only the question of rise and decline of tourism, but also of change of place qualities. How can the variability of resort development be further qualified and explained? We develop the concept of "touristic capital" of resorts in order to analyse the variable trajectories of resorts over time. It is suggested resorts engage a specific touristic capital within a global tourism field. The differential capacity of accumulating and engaging resources, governance, image, monetary incomes urban qualities and knowledge in the tourism field is seen as a significant aspect of resort development. The concept dwells on different disciplinary achievements within geography, economics, sociology and political science.
Keywords: Resort development; Touristic capital; Tourism field; Touristification; urbanisation